2015
DOI: 10.21273/hortsci.50.10.1447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon in the Nutrient Solution for Three Horticultural Plant Families on the Vegetative Growth, Cuticle, and Protection Against Botrytis cinerea

Abstract: The silicon (Si) percentage in the dry matter of plants is between 0.1% and 10%, and even though its role in the metabolism of plants is not absolutely clear, Si’s positive effects on plant nutrition and plant protection against both biotic and abiotic stress are well documented. However, Si is not considered to be an essential element, so it is not always present in nutrient solutions. In this paper, an experiment was carried out in the University of Almeria’s greenhouse with hydroponic lettuce, tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The buffer capacity of the organic matter that constitutes the CF was likely the reason that, despite the lower EC and pH, the CF was more suitable for blueberry plants compared with sand. These data corroborate the growth benefits found by Pozo et al (2015), who applied 0.65 mM Si in the nutrient solution and found, in addition to increased protection against Botrytis cinerea, a significant increase in the growth parameters of five families of plants grown in CF. On the other hand, Morikawa and Saigusa (2004), using river water containing between 0.66 and 1 mol · m -3 Si for irrigation, found that blueberry plants accumulated 3.1 and 5.4 times more Si than N in young and old leaves, respectively, thus classifying blueberry as an Si accumulator plant.…”
Section: Expt 1: Application Of Silicon In the Nutrient Solutionsupporting
confidence: 89%
See 1 more Smart Citation
“…The buffer capacity of the organic matter that constitutes the CF was likely the reason that, despite the lower EC and pH, the CF was more suitable for blueberry plants compared with sand. These data corroborate the growth benefits found by Pozo et al (2015), who applied 0.65 mM Si in the nutrient solution and found, in addition to increased protection against Botrytis cinerea, a significant increase in the growth parameters of five families of plants grown in CF. On the other hand, Morikawa and Saigusa (2004), using river water containing between 0.66 and 1 mol · m -3 Si for irrigation, found that blueberry plants accumulated 3.1 and 5.4 times more Si than N in young and old leaves, respectively, thus classifying blueberry as an Si accumulator plant.…”
Section: Expt 1: Application Of Silicon In the Nutrient Solutionsupporting
confidence: 89%
“…However, the beneficial effects of Si have been published both in plant protection (Imtiaz et al, 2016;Luyckx et al, 2017;Urrestarazu et al, 2016;Van Bockhaven et al, 2013) and in mineral nutrition (Kaya et al, 2006;Mengel and Kirkby 2000;Zhu and Gong, 2014). During the past few decades (Heine et al, 2005;Sonneveld and Straver, 1994;Sonneveld and Voogt, 2009) and, more recently (Pozo et al, 2015), Si is considered in the nutrient solution for horticultural and ornamental crops. Both Si and citric acid are active substances accepted in organic farming in Europe (DOUE, 2008) and the United States (USDA Organic, 2015).…”
mentioning
confidence: 99%
“…It has previously been shown that Si can mitigate botrytis infection in greenhousegrown crops. Supplying 0.67 mM Si in a hydroponic nutrient solution reduced the leaf area infected by botrytis 3 d postinoculation in lettuce (Lactuca sativa L.), tomato, and pepper (Capsicum annuum L.) (Pozo et al, 2015). Flowers are susceptible to botrytis infection, especially during transport from the greenhouse to the final retail destination.…”
Section: Resultsmentioning
confidence: 99%
“…Structural silicon provides physical protection to plants against microbial infection and insect attack as well as redugin the quality of the tissue to the predating organisms 23 . In lettuce, tomato, and pepper plants, a beneficial effect against Botrytis cinerea was observed when the nutrient solution containig Si was used 38 . The physical, biochemical and molecular defense mechanisms in plants mediated by Si are the following: a) Si induces resistance against a wide range of diseases by acting as a physical barrier, which is based on pre-formed defense barriers before pathogen infection, b) Si-induced biochemical resistance during plant-pathogen interactions involves production, and regulating the complex network of signal pathways, c) Si may act at a molecular level to regulate the expression of genes involved in the defense response 39 .…”
Section: Mechanism Of Silicon Against Biotic Stressmentioning
confidence: 99%